Sisters : myth and reality of Anabaptist, Mennonite, and Doopsgezind women ca. 1525-1900 - Veen, Mirjam van (Brill's series in church history ;, 2014)
Imagology, not gender studies, sets the stage for the analysis of the perceptions of the European Anabaptist/Mennonite 'sisters', from the 16th-19th centuries, within their religious, moral, cultural and social landscapes of Austria, Belgium, Germany, the Netherlands, Poland, Switzerland, and the Ukraine.